Maurice the old motor car: bedtime books - Spurgeon, Maureen (Brown Watson Italy, 1993)
"Maurice the Old Motor Car" tells the charming story of Maurice, a vintage car who feels forgotten and outdated in a world of shiny new vehicles. Despite his age, Maurice has a lot of heart and memories from his past adventures. When a young child discovers him, they embark on a journey together, showcasing the importance of friendship, nostalgia, and appreciating the value of things that may seem old but hold great stories and charm.